Determination and estimation of the straight the straight line parameters with the compass coupling - A.V. Mastipanova (Academy of Cognitive and Natural Sciences, 2006)
A combined method of interpretation of a fluent curve Itne by the line with compass coupling and determination of its parameters and calculation precision estimation was suggested by the author.